Study on Caste, Gender and Patriarchy in Meena Kandasamy’s Works: Exploring Social Injustice and Feminism in Meena Kandasamy's Works (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Meena Kandasamy is a developing twentieth-century Dalit poet, fiction author, interpreter, columnist, and social dissident. Her first assortment of poetry, Touch (2006) is a blistering, activist assault on the propagation of the social mistreatment of the Indian ladies. It talks about the issues of caste, gender, sex, and social segregations of the underestimated Indian ladies. Kandasamy is a poet, interpreter and dynamic extremist from Chennai. As a contemporary Indian woman author Kandasamy is anguished to observe the deep-rooted social practices like unapproachability dependent on caste framework existing in Indian society. She voices her displeasure against caste-based shamefulness which has impeded the underestimated to the dehumanized condition as they are exposed to mistreatment and mortification. Her two assortments of poetry Touch (2006) and Ms Militancy (2010) depict the genuine picture of the underestimated in Indian society, as it were, the centre of her work around neediness, persecution, bad form, caste obliteration, phonetic character and aches and difficulties of ladies. Maht, Mohan Lal in his article, Meena Kandasamy's Touch An Articulation of the Voice of the Marginalized watched Casteism is an old social insidious which is utilized to enslave the lower layer of the hierarchal social structure of Indian society.